Analisis Pemanfaatan Pelayanan Kesehatan pada Pemeriksaan Kualitas Air di Labkesda Kabupaten Lampung Selatan - Astari, Yulia; Wayan, Wayan; Yanti, Dhiny Easter; Samino, Samino; Sari, Fitri Eka (Universitas Malahayati, 2025)
ABSTRACT Based on the results of the South Lampung Regency LABKESDA report, of the 1,071,727 South Lampung residents whocarry out water quality checks is still low, namely in 2022 there are 154 (0.014%) who carry out water quality checks and in 2023 there are 171 (0.015%) who carry out water quality checks. water quality inspection. Thepurpose of this research is to determine the analysis of the use of health services in water quality checks atLABKESDA South Lampung Regency in 2024. This type of research is qualitative research with a case study approach. There were 7 informants for this research, namely, the Head of the South Lampung District Health Service,the Head of Administration for the South Lampung LABKESDA, Community Health Center Officers, Clinic Officers,PDAM Officers, and 2 members of the public. Informants were taken using purposive sampling. Datacollection uses in-depth interview techniques and data analysis techniques using Content Analysis. The results of theresearch show that the Analysis of Health Service Utilization in Water Quality Inspections at LABKESDA, South Lampung Regency, Obstacles and Obstacles are still quite high funding and long distances for the community toreach. The benefits can improve health rates, especially in the use of clean water sanitation. The community isconfident and supports the water quality inspection services at LABKESDA South Lampung. Accessibility in checkingwater quality regarding distance is very affordable, but for sub-district areas it is quite far. The availability offacilities and infrastructure at LABKESDA is good and adjusted to applicable regulations. The suggestion of thisresearch is that the government can pick up the ball and increase cooperation with all Community Health Centersand Pustu to facilitate the implementation of good services. Keywords: Facilities, Obstacles, Utilization, LABKESDA ABSTRAK Berdasarkan hasil laporan LABKESDA Kabupaten Lampung Selatan bahwa dari 1.071.727 jumlah penduduk Lampungselatan yang melakukan pemeriksaan kualitas air masih rendah, yaitu pada tahun 2022 terdapat 154 (0,014%) yangmelakukan pemeriksaan kualitas air dan pada tahun 2023 terdapat 171 (0,015%) yang melakukan pemeriksaankualitas air. Tujuan dilakukannya penelitian ini untuk mengetahui Analisis pemanfaatan pelayanan kesehatan pada pemeriksaan kualitas air di LABKESDA Kabupaten Lampung Selatan Tahun 2024. Jenis penelitian ini yaitu penelitian kualitatif dengan pendekatan Studi kasus. Terdapat 7 informan penelitian ini yaitu, Kepala DinasKesehatan Kabupaten Lampung Selatan, Kepala Tata Usaha LABKESDA Lampung Selatan, Petugas Puskesmas, PetugasKlinik, Petugas PDAM, dan 2 orang masyarakat. Pengambilan informan dengan cara Purposive Sampling. Pengumpulandata menggunakan teknik wawancara mendalam dan teknik analisis data menggunakan Content Analysis. Hasilpenelitian bahwa Analisis Pemanfaatan Pelayanan Kesehatan Pada Pemeriksaan Kualitas Air di LABKESDA Kabupaten Lampung Selatan Hambatan Dan Kendala yaitu masih cukup tingginya pembiayaan dan jarak yang jauhuntuk dijangkau masyarakat. Manfaatnya dapat meningkatkan angka kesehatan terutama dalam penggunaan sanitasiair bersih. Keyaninan masyarakat yakin dan mendukung pelayanan pemeriksaan kualitas air di LABKESDA Lampungselatan. Aksebilitas dalam pemeriksaan kualitas air terkait jarak sangat terjangkau namun untuk daerah kecamatan agak jauh. Ketersediaan fasilitas sarana dan prasarana yang ada di LABKESDA sudah baik dan disesuaikan dengan peraturan yang berlaku. Saran penelitian ini, yaitu agar pemerintah dapat jemput bola danmenambah kerjasama kepada seluruh Puskesmas dan Pustu untuk mempermudah terlaksananya pelayanan dengan baik. Kata Kunci: Fasilitas, Hambatan, Pemanfaatn, LABKESDA